2019
DOI: 10.3390/w11071453
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Patterns of the Extreme Precipitation across the Tibetan Plateau (1986–2015)

Abstract: The Tibetan Plateau is one of the most vulnerable areas to extreme precipitation. In recent decades, water cycles have accelerated, and the temporal and spatial characteristics of extreme precipitation have undergone dramatic changes across the Tibetan Plateau, especially in its various ecosystems. However, there are few studies that considered the variation of extreme precipitation in various ecosystems, and the impact of El Niño-Southern Oscillation (ENSO), and few researchers have made a quantitative analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Encompassing approximately 25% of China's mainland, the TP primarily includes the regions of north-western Sichuan, Qinghai, and Tibet. As 'Asia's water tower' [41], the Plateau possesses a typical thermal/moisture gradient from the southeast to northwest due to the elevation and monsoonal winds, and it includes a range of climate-sensitive vegetation along the climate change characteristics, from subtropical and tropical forests to alpine deserts. Specifically, the annual mean total precipitation increases from 16 mm in the northwest to 1764 mm in the southeast, as observed during the period of 1981-2011, with a corresponding variation gradient in the annual mean air temperature increasing from −5.0 • C in the northwest to 15.5 • C in the southeast [42].…”
Section: Study Areamentioning
confidence: 99%
“…Encompassing approximately 25% of China's mainland, the TP primarily includes the regions of north-western Sichuan, Qinghai, and Tibet. As 'Asia's water tower' [41], the Plateau possesses a typical thermal/moisture gradient from the southeast to northwest due to the elevation and monsoonal winds, and it includes a range of climate-sensitive vegetation along the climate change characteristics, from subtropical and tropical forests to alpine deserts. Specifically, the annual mean total precipitation increases from 16 mm in the northwest to 1764 mm in the southeast, as observed during the period of 1981-2011, with a corresponding variation gradient in the annual mean air temperature increasing from −5.0 • C in the northwest to 15.5 • C in the southeast [42].…”
Section: Study Areamentioning
confidence: 99%
“…The understanding of the spatial and temporal patterns of precipitation change is very important to a country, such as China, where the available water per person is only one-third of the world average [4]. Spatial and temporal changes in precipitation have been studied for different regions in China, for example, Southwestern China [5], Northwestern China [6], the Yangtze River Delta [7], the Zhujiang River Basin [8], and other specific regions [9][10][11][12][13][14][15][16]. These results agree with the literature in that the observed changes in precipitation extremes are much less spatially coherent and statistically significant compared to observed changes in temperature extremes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the Asian summer monsoon affects precipitation in southern regions of the TP [29,53]. As shown in Table 8, the South Asian summer monsoon index (SASMI) has a positive correlation with PRCPTOT and R10 mm, indicating that the South Asian summer monsoon has considerable influence on precipitation variation.…”
Section: Relationship Between Extreme Precipitation Changes and Monsomentioning
confidence: 78%
“…China China Previous studies have indicated that the annual total precipitation is well correlated with extreme precipitation [29,32,34,53]. Figure 13b indicates a strong correlation between total precipitation and each of the precipitation indices (except CDD), of which R95p, R10mm, and R20mm showed the best correlation with total precipitation with a correlation coefficient of >0.70 (p < 0.01).…”
Section: Southwesternmentioning
confidence: 83%